Ocena zasobów informacyjnych raportów środowiskowych przedsiębiorstw - Brzozowski, Tomasz (Estimation of information stores of enterprises’ Environmental Reports, 2008)
The practice to publish environmental reports becomes more and more popular among companies in Poland. This article describes and compares environmental reports, especially towards used environmental indicators. Owing to this research conclusions about environmental reports’ quality have formulated. It appears that reports prepared by companies are considerably different. It particularly refers to environmental indicators used in the analyzed reports.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 33-44